Diskursus Politik Dalam Proses Pemekaran Wilayah Pantai Timur - Zakiyah, Nurul; Minako, Muchlis (Indonesian Journal of Social Development, 2023)
The purpose of my research is to analyze the regional development of Pantai discourse. Timur Calls for Separation of Ogan Kommering Illil Autonomous Region A district that has undergone a long journey of various local political elites. the method of Investigation using the qualitative descriptive method, a more urgent investigative strategy Searching for meaning using the Pareto theory of political elites (1984-1923). Data is collected by: Interview methodology, data collection, data reduction, data presentation and conclusions. Of As a result of this research, (1) it is the discourse of Pantai Timur development Community needs have led local elites to build means of communication Support at government and community levels. (2) New establishment process This district is subject to many restrictions due to changes in the central government's laws. 2014. Hence the aspirations of the political elite and the support of the community There is still a long way to go in the process and process of creating new districts to acquire and acquire positions. and power in the new governing body.